Hadith Prohibiting Binge Eating Disorder in Sigmund Freud’s Psychoanalytic Perspective - Hartati, Hartati; Anam, Khoirul; Malik, Ahmed Abdul; Dwi Yanti, Nurul Azizah (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
This article discusses about the importance of the investigation of overeating topic to be examined, since it has caused a lot of victims. The main causes to it are obesity, cardiovascular, and bad diet. The prophet salallahu ‘alaihi wassalam (d.11 H) had given hadith about the correct and appropriate way on eating and drinking. This problem has become the question as well as the purpose of this hadith. This article hinges on the quality and the quantity of the hadith prohibiting Binge Eating Disorder in Sigmund Freud’s Psychoanalytic Perspective. The method of data collection in this study is library research which involves the review of primary book and its syarah. The supported resources are derived from journal article, book, and relevant literature. Data was analysed by using Psychoanalytic perspective of Sigmund Freud. The result shows that this hadith can be classified as marfu` qauli with the narration of Bil Ma’na. Ibnu Mājah’s narration is Mubham, which means there is no irregularities in this type of sanad, hence: this hadith is not fulfilling the ṣaḥīḥ criteria, or this hadith can be grouped as ḍa`īf. However, according to imam Tirmiżi and imam Aḥmad bin Hanbal, the two sanad are considered as having no irregularities, so that this hadith can then be claimed as ḥasan li ghairihi. The quantity of this hadith is Ahad with absolute gharib category due to its single narration of its beginning of the sanad (the companion Miqdam bin Ma’di Karib). The matan of hadith narrated by Miqdam bin Ma’di Karib consists of advice and recommendation for human to be able to manage uncontrollable willing (Id). The strong willing is controlled by ego, and it is supposed to be submitted to the commands of the superego/moral. All of the three are parts of the conscious mind and the unconscious mind of Sigmund Freud’s psychoanalytic. In addition, Binge Eating Disorder (BED) can be derived from emotional eating, mindless eating, and kuchisabishi.